The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmicb.2022.852434
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Characteristics of Plasmid-Borne mcr-9 in Salmonella enterica Serotype Typhimurium and Thompson in Zhejiang, China

Abstract: Salmonella enterica is a zoonotic food-borne pathogen threatening public health around the world. As is the case with many other pathogens, the spread of mobilized colistin resistance (mcr) alleles is of grave concern. In this study, totally 689 clinical Salmonella isolates were collected from a local hospital in Hangzhou, Zhejiang Province, China between 2009 and 2018. Resistance genes were screen by PCR. Two mcr-9-positive Salmonella strains S15 and S639 were identified which belong to serotype Typhimurium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…Our results highlight the problematic nature of measuring colistin resistance in the lab, consistent with several studies that found that the presence of mcr-9 gene is not sufficient to confer colistin resistance [50,74,75]. Nevertheless, over-expression of mcr-9 consistently generates clinically relevant resistance in E. coli [44].…”
Section: Discussionsupporting
confidence: 87%
“…Our results highlight the problematic nature of measuring colistin resistance in the lab, consistent with several studies that found that the presence of mcr-9 gene is not sufficient to confer colistin resistance [50,74,75]. Nevertheless, over-expression of mcr-9 consistently generates clinically relevant resistance in E. coli [44].…”
Section: Discussionsupporting
confidence: 87%
“…Three MDR Salmonella strains were recovered from the strain bank and isolated with Salmonella agar (CHROMagar Company, Paris, France); strains were identified using the Vitek-II system (bioMérieux, Lyon, France). The genomic DNA from each strains was extracted by boiling and freeze-thawing processes, and the resulting supernatant was recovered for use as the PCR template ( Doyle et al, 2012 ; Ding et al, 2020 ; Fan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, selective pressure from the overuse or misuse of both antimicrobials has resulted in the emergence of carbapenem- and colistin-resistant Enterobacteriaceae (CRE) ( Nang et al, 2019 ; Octavia et al, 2020 ). Regarding Salmonella isolates, recent studies have demonstrated their resistance to these critical antimicrobial drugs ( Wang et al, 2017 ; Fan et al, 2022 ; Zhang et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%